Pengaruh Penerapan Layanan Samsat Drive Thru Dan Samsat Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kota Palembang - Kinanti, Asih; Anggraini, Leriza Desitama; Meiriasari, Vhika (Fakultas Ekonomi Prodi Akuntansi, 2024)
The manner in which taxpayers complete their tax obligations is known as compliance with the laws and regulations governing taxation. The potential to impact taxpayer compliance exists for both external and internal factors. Motivation from within that is connected to an individual's special qualities is known as internal motivation, and it is what drives someone to pay their taxes. All the same, it is an external factor, originating from the outside; examples of external factors are the surrounding environment and unsupportive conditions. This study looks at the impact of mobile and drive-through SAMSAT services on taxpayer compliance with motor vehicles. Palembang City motorists who file taxes were given access to a Google Form survey. The purpose of the survey was to randomly select one hundred respondents. It is possible to analyze data using quantitative approaches. The impact of drive-through SAMSAT on motor vehicle tax compliance in Palembang City is nil (prob 0.334 > alpha = 0.05), but mobile SAMSAT has a considerable impact (prob 0.021 < alpha = 0.05). These were the outcomes of the analysis. When SAMSAT travel and drive-through are coupled, there is also a significant impact on motor vehicle tax compliance in Palembang City (prob = 0.000 < alpha = 0.05). Keywords: SAMSAT Drive Thru, SAMSAT Keliling, Taxpayer Compliance.